Silicon nanoparticles and indole butyric acid positively regulate the growth performance of Freesia refracta by ameliorating oxidative stress under chromium toxicity - Ahsan, Muhammad; Radicetti, Emanuele; Jamal, Aftab; Ali, Hayssam M.; Sajid, Mateen; Manan, Abdul; Bakhsh, Ali; Naeem, Muhammad; Khan, Jawad Ahmad; Valipour, Mohammad (Frontiers in Plant Science, 2024)
Chromium (Cr) toxicity hampers ornamental crops' growth and post-harvest quality, especially in cut flower plants. Nano-enabled approaches have been developing with phenomenal potential towards improving floricultural crop production under heavy metal-stressed conditions. The current pot experiment aims to explore the ameliorative impact of silicon nanoparticles (Si-NPs; 10 mM) and indole butyric acid (IBA; 20 mM) against Cr stress (0.8 mM) in Freesia refracta. The results showed that Cr stress significantly reduced morphological traits, declines roots-stems biomass, abridged chlorophyll (14.7%) and carotenoid contents (27.2%), limits gas exchange attributes (intercellular CO2 concentration (Ci) 24.8%, stomatal conductance (gs) 19.3% and photosynthetic rate (A) 28.8%), condensed proline (39.2%) and total protein (40%) contents and reduced vase life (15.3%) of freesia plants by increasing oxidative stress. Contrarily, antioxidant enzyme activities, MDA and H2O2 levels, and Cr concentrations in plant parts were remarkably enhanced in Cr-stressed plants than in the control. However, foliar supplementation of Si-NPs + IBA (combined form) to Cr-stressed plants increased defense mechanism and tolerance as revealed by improved vegetative and reproductive traits, increased biomass, photosynthetic pigments (chlorophyll 30.3%, carotenoid 57.2%) and gaseous exchange attributes (Ci 33.3%, gs 25.6%, A 31.1%), proline (54.5%), total protein (55.1%), and vase life (34.9%) of metal contaminated plants. Similarly, the improvement in the activities of peroxidase, catalase, and superoxide dismutase was recorded by 30.8%, 52.4%, and 60.8%, respectively, compared with Crstressed plants. Meanwhile, MDA (54.3%), H2O2 (32.7%) contents, and Cr levels in roots (43.3), in stems (44%), in leaves (52.8%), and in flowers (78.5%), were remarkably reduced due to combine application of Si-NPs + IBA as compared with Cr-stressed nontreated freesia plants. Thus, the hypothesis that the synergistic application of Si-NPs + IBA will be an effective approach in ameliorating Cr stress is authenticated from the results of this experiment. Furthermore, the study will be significant since it will demonstrate how Si-NPs and IBA can work synergistically to combat Cr toxicity, and even when added separately, they can improve growth characteristics both under stressed and un-stressed conditions.